2018
DOI: 10.1111/jphp.12862
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation of adipocytes to osteoblasts: potential for orthopaedic treatment

Abstract: Objectives As both adipocytes and osteoblasts originate from the same pool of mesenchymal stem cells, increasing clinical evidence has emerged of the plasticity between the two lineages. For instance, the downregulation of osteoblast differentiation and upregulation of adipogenesis are common features of conditions such as multiple myeloma, obesity and drug-induced bone loss in diabetes mellitus. However, despite in-vitro and in-vivo observations of adipocyte transdifferentiation into osteoblasts, little is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 127 publications
(262 reference statements)
0
10
0
Order By: Relevance
“…For orthopedic disorders such as osteoporosis and bone dysplasia, transdifferentiation of myoblasts or adipocytes into osteoblasts also has the potential to provide a novel therapy. 17,24 Many studies have now provided a proof-of-concept for therapeutic transdifferentiation.…”
Section: Tr An S D Ifferentiati On Ther Apy For Non C An Cer Dis E a S E Smentioning
confidence: 99%
See 3 more Smart Citations
“…For orthopedic disorders such as osteoporosis and bone dysplasia, transdifferentiation of myoblasts or adipocytes into osteoblasts also has the potential to provide a novel therapy. 17,24 Many studies have now provided a proof-of-concept for therapeutic transdifferentiation.…”
Section: Tr An S D Ifferentiati On Ther Apy For Non C An Cer Dis E a S E Smentioning
confidence: 99%
“…The differentiation of MSCs into preadipocytes during adipogenesis is induced by the action of insulin, dexamethasone, cyclic AMP, and bone morphogenetic protein 4. 24 Transcription factors that contribute to adipocyte differentiation include CCAAT/enhancer binding protein-α (C/EBPα), C/EBPβ, and peroxisome proliferator-activated receptor-γ (PPARγ).…”
Section: Os Teosarcoma C Sc Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Transdifferentiation, also known as lineage reprogramming, is the conversion of one mature somatic cell into another mature somatic cell without going through a pluripotent state [11]. Several in vitro studies using human BMSCs or mature osteoblasts derived from trabecular bone have demonstrated the occurrence of transdifferentiation between osteoblastic and adipocytic phenotypes in response to extrinsic factors [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%